PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL NUMBERED HEAD TOGETHER (NHT) DI KELAS IV - Rosy Kurnia Nurhasanah; Yunisrul Yunisrul (Universitas Negeri Padang, 2022)
This research aims to explain the results of students' learning in integrated thematic learning using a cooperative model of Numbered Head Together (NHT) type in grade IV of state primary school 30 Desa Baru. This research is a class action study (PTK) using a qualitative and quantitative approach. The subjects of this study were class teachers as observer, researchers as practitioners, and 20 grade IV students of state primary school 30 Desa Baru. The results of this study are: (1) The percentage of RPP assessments increased from 84.6% in cycle I to 94% in cycle II. (2) In the teacher aspect increased from 82.7% in cycle I to 93.7% in cycle II. (3) In the student aspect increased from 82.7% in cycle I to 93.7% in cycle II. (4) Study results in cycle I obtain a completion percentage of 45% to 90% in cycle II.